DESIGNING AUTHENTIC ASSESSMENTS FOR ASSESS STUDENTS’ HIGHER-ORDER THINKING SKILL IN WRITING: A NARRATIVE REVIEW - Dian Riani Said; Sirwanti Sirwanti; Fahriadi Muhdar; Hamka Hamka (Bajang Institute, 2023)
Authentic assessment has an important role in measuring students' higher order thinking skills in writing. However, designing an authentic assessment to measure higher order thinking skills in writing is a challenge. This abstract outline the steps needed to design an authentic assessment that is effective in measuring students' higher-order thinking skills in writing. The method used includes identifying learning objectives, determining assessment criteria, developing authentic writing assignments, and carrying out assessments that involve clear scoring rubrics. Current research and practice in this field is reviewed to provide a sound theoretical foundation. This abstract also discusses the benefits and challenges of using authentic assessment, including the development of assessments that are relevant to curriculum needs and competency-based learning. By paying attention to these aspects, a better understanding is gained on how to design effective authentic assessments to measure students' higher-order thinking skills in writing, thereby enabling the development of better learning strategies and improving student learning outcomes.